Ambiguous angels : gender in the novels of Galdós - Jagoe, Catherine (Berkeley : University of California Press, 1994)
The contradictory nature of the work of Benito Pérez Galdós, Spain's greatest modern novelist, is brought to the fore in Catherine Jagoe's innovative and rigorous study. Revising commonly held views of his feminism, she explores the relation of Galdós's novels to the "woman question" in Spain, arguing that after 1892 the muted feminist discourse of his early work largely disappears. While his later novels have been interpreted as celebrations of the emancipated new woman, Jagoe contends that they actually reinforce the conservative, bourgeois model of frugal, virtuous womanhood--the angel of the house. Using primary sources such as periodicals, medical texts, and conduct literature, Jagoe's examination of the evolution of feminism makes Ambiguous Angels valuable to anyone interested in gender, culture, and narrative in nineteenth-century Europe.
1. Woman's Mission as Domestic Angel. Bourgeois Gender Ideology and the angel del hogar. Women Writers and the Domestic Ideal. Problems and Paradoxes -- 2. Galdos and the Woman Question. Galdos's Affiliations with the prensa femenina. Galdosian Reflections on Woman's Place. Engendering the Novel: Galdos's Vision of Realism -- 3. Suffering Women. Gender and Representation in the Early Novels. The Bird-Angel in Gloria. Leon Roch's Wife -- 4. Struggling with the Angel. Consuming Passions: Luxury and the Sexual Politics of Representation in the Contemporary Novels. In Search of the Ideal Woman: Educating Manso. The Angel in Mind: Rereading Fortunata y Jacinta -- 5. Gender Trouble. Feminism and the Fin de Siecle in Spain. Tristana and the "Legless Angel of Victorian Romance" Seeing the Light: Halma's Conversation -- 6. New Women. Decadence and the New Woman. The novelas dialogadas: La loca de la casa and El abuelo. Teaching Women -- Appendix 1. List of Galdos's Novels -- Appendix 2. "La mision de la mujer."
Includes bibliographical references (pages 217-229) and index.
Print version record.
English.
JSTOR
Keywords: Pérez Galdós, Benito, -- 1843-1920 -- Criticism and interpretation; Pérez Galdós, Benito, -- 1843-1920; Pérez Galdós, Benito, -- (1843-1920) -- Critique et interprétation.; Women in literature; Sex role in literature; Femmes dans la littérature.; Rôle selon le sexe dans la littérature.; Sex role in literature; Women in literature; Romans; Sekseverschillen; Spaans; Romance Literatures; Languages & Literatures; Spanish Literature; Femmes -- Dans la littérature.; Rôle selon le sexe -- Dans la littérature.; Sexe dans la littérature.; 1892.; 19th century; angel of the house; benito prez galds; bourgeois model; conduct literature; conservative; culture; emancipated new woman; europe; evolution of feminism; feminism; frugal; gender; medical texts; muted feminist discourse; narrative; periodicals; spain; studying writing; virtuous womanhood; woman question; Criticism, interpretation, etc